In situ incubation of iron(II)-bearing minerals and Fe(0) reveals insights into metabolic flexibility of chemolithotrophic bacteria in a nitrate polluted karst aquifer - Visser, Anna-Neva; Martin, Joseph D.; Osenbrück, Karsten; Rügner, Hermann; Grathwohl, Peter; Kappler, Andreas (Science of the Total Environment, 2024)
Groundwater nitrate pollution is a major reason for deteriorating water quality and threatens human and animal health. Yet, mitigating groundwater contamination naturally is often complicated since most aquifers are limited in bioavailable carbon. Since metabolically flexible microbes might have advantages for survival, this study presents a detailed description and first results on our modification of the BacTrap© method, aiming to determine the prevailing microbial community's potential to utilize chemolithotrophic pathways. Our microbial trapping devices (MTDs) were amended with four different iron sources and incubated in seven groundwater monitoring wells for ∼3 months to promote growth of nitrate-reducing Fe(II)-oxidizing bacteria (NRFeOxB) in a nitrate-contaminated karst aquifer. Phylogenetic analysis based on 16S rRNA gene sequences implies that the identity of the iron source influenced the microbial community's composition. In addition, high throughput amplicon sequencing revealed increased relative 16S rRNA gene abundances of OTUs affiliated to genera such as Thiobacillus, Rhodobacter, Pseudomonas, Albidiferax, and Sideroxydans. MTD-derived enrichments set up with Fe(II)/nitrate/acetate to isolate potential NRFeOxB, were dominated by e.g., Acidovorax spp., Paracoccus spp. and Propionivibrio spp. MTDs are a cost-effective approach for investigating microorganisms in groundwater and our data not only solidifies the MTD's capacity to provide insights into the metabolic flexibility of the aquifer's microbial community, but also substantiates its metabolic potential for anaerobic Fe(II) oxidation.
CRIS-Team Scopus Importer:2024-04-05
Keywords: Chemolithotrophic growth; Corrosion; Karst groundwater; Nitrate; Nitrate-reducing Fe(II) oxidation